Review of Sharia Economic Law on the Empowerment and Arrangement of Street Vendors in Palembang City - Utami, Iftitah (Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study is to examine the Role of the Palembang City Tourism Service in Implementing Palembang Mayor's Regulation Number 37 of 2017 in Night Culinary Micro Enterprises in the Sudirman Pedestrian Area of Palembang City based on Sharia economic law. This research is motivated by the many economic activities carried out in the Sudirman Pedestrian Center of Palembang City, resulting in the arrangement of traders not running well. The method used in this study is a qualitative method with a field research. This research is called empirical normative. The types of data in this study are primary and secondary. Data collection was done by interviewing and documenting. Data analysis was carried out descriptively, and qualitatively using deductive method. The results of the study concluded that the ​implementation of Palembang Mayor's Regulation Number 37 of 2017 provides an opportunity to strive, grow and develop business capabilities, and realize a city that is clean, safe, neat and beautiful. In economic law implementing Palembang Mayor's Regulation Number 37 of 2017 has been in accordance with the principles of sharia economic law, namely maslahah​ which aims to improve welfare to street vendors in the sudirman pedestrian area.​